The features of hybrid dysgenesis syndrome manifestation in some Drosophila melanogaster stocks - Городнянський, І. Д.; Воробйова, Л. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The expression of hybrid dysgenesis in F1 and F2 offspring of cyclic crosses between Oregon-R, Harwich and whd Drosophila melanogaster stocks, presumably differing by the presence of certain mobile genetic elements has been studied. The hybrid dysgenesis degree was evaluated in accordance with the test for gonad atrophy. The data obtained suggest the presence of functionally active copies of transposable genetic element hobo in the genotype of Oregon-R stock from the collection of the Genetics and Cytology department of V.N.Karazin KhNU. The possibility of presence of hobo or other element capable to cause hybrid dysgenesis syndrome in genotype of whd stock in addition to the P-element is discussed. The features of whd stock in the P-M system of hybrid dysgenesis are analyzed.